Overview of the Implementation of Special Education Professional Development Policy in Indonesia - Darma Kadir; Nurwidia Ningsih; Junaeda Junaeda; Abd. Hadis; Faisal Faisal (ANTHOR: Education and Learning Journal, 2026)
This study aims to examine the professional development policy for special education teachers in Indonesia and analyze its implementation, challenges, and implications in supporting inclusive education. The study employed a qualitative approach with a literature review method through analysis of policy documents, scientific journals, and research reports for the 2016–2025 period. Data were analyzed qualitatively through data reduction, data presentation, and conclusion drawing, and strengthened with thematic analysis. Data validity was maintained through source triangulation. The study results indicate that the professional development policy for special education teachers has been directed through strategic programs, such as Teacher Professional Education (PPG), Continuing Professional Development (PKB), and the Merdeka Mengajar digital platform. Conceptually, this policy aligns with contemporary professional development approaches, inclusive pedagogy, adaptive expertise, and equity-oriented policy. However, its implementation has not been optimal due to gaps between policy and practice in the field, such as low relevance of training materials, the dominance of theoretical approaches, limited access in remote areas, low technological literacy, and high administrative burdens on teachers. This study highlights the importance of contextual, collaborative, and sustainable professional development based on teachers’ real needs. Strengthening institutional collaboration, integrating technology, and simplifying administrative systems are recommended to improve the quality of special education services in Indonesia.